EFEKTIVITAS LKPD BERBASIS ACE UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Nela Sari Yolanda Nela; Khurnia Budi Utami; Dina Novarina Perdana; Nurul Hasna Putri (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
Enjoyable mathematics learning is the hope of every student. Where learning facilitates students to discover the principles of the material studied in a meaningful way. Teachers can do this by designing interesting learning activities and encouraging students to use their thinking patterns. For this reason, it is necessary to develop mathematics learning tools that can provide opportunities for students to construct knowledge and improve their learning outcomes. So an ACE-based learning tool was developed which is expected to achieve this target. The goal to be achieved from this development effort is to produce effective ACE-based mathematics learning tools. The learning developed is in the form of Student Worksheets (LKPD). The subjects of this research were students of class XI Culinary Arts at SMK N 6 Padang, class This learning tool is effective in terms of student learning outcomes. In this case, the learning outcomes of experimental class students were 87.50% of students scored above the KKM, while 60% of control class students scored above the KKM. Based on these results, it can be concluded that the ACE-based learning tools for mathematics learning in class XI Catering 2 can be declared effective.